2014
DOI: 10.1155/2014/162754
|View full text |Cite
|
Sign up to set email alerts
|

Association between Severe Upper Limb Spasticity and Brain Lesion Location in Stroke Patients

Abstract: Association between the site of brain injury and poststroke spasticity is poorly understood. The present study investigated whether lesion analysis could document brain regions associated with the development of severe upper limb poststroke spasticity. A retrospective analysis was conducted on 39 chronic stroke patients. Spasticity was assessed at the affected upper limb with the modified Ashworth scale (shoulder, elbow, wrist, and fingers). Brain lesions were traced from magnetic resonance imaging performed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 18 publications
5
43
1
2
Order By: Relevance
“…Caudate nucleus injury was related to motor recovery in the lower limbs (Lee et al., ). Neuronal injury in the corona radiata, caudate nucleus, and putamen of patients with chronic stroke changed their walking speed (Jones et al., ; Picelli et al., ). Our results showed that involvement of the globus pallidus and putamen was related to poor recovery in stroke patients at 3 months after onset.…”
Section: Discussionmentioning
confidence: 99%
“…Caudate nucleus injury was related to motor recovery in the lower limbs (Lee et al., ). Neuronal injury in the corona radiata, caudate nucleus, and putamen of patients with chronic stroke changed their walking speed (Jones et al., ; Picelli et al., ). Our results showed that involvement of the globus pallidus and putamen was related to poor recovery in stroke patients at 3 months after onset.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors found to be related to the development of post-stroke spasticity are left-sided weakness, a history of smoking, low quality of life, manual activities before stroke, a previous history of stroke, and extensive lesions (Leathley et al, 2004;de Cássia do Reis Moura et al, 2009;Urban et al, 2010). Lastly, lesion mapping-based analysis of the association of post-stroke spasticity with stroke lesions showed involvement of the insula, thalamus, basal ganglia and white matter tracts (internal capsule, corona radiata, external capsule, superior longitudinal fasciculus) (Picelli et al, 2014d).…”
Section: Predictors Of Post-stroke Spasticitymentioning
confidence: 99%
“…после инсульта [4]. ПС имеет тенденцию к нарастанию в течение первых месяцев после инсульта, что ведет к формированию контрактур, затрудняет самообслуживание, делает уход за пациентом обременительным и оказывает отрицательное влияние на качество жизни больных и их семей [5][6][7][8]. Наличие спастичности требует проведения дополнительных реабилитационных мероприятий, что приводит к увеличению прямых затрат, связанных с ОНМК.…”
Section: спастические расстройстваunclassified